(3KHJ CeI GdNGdb HfJ CMeO GdHjLhQis
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg hHYO abO MVQJ UGMHI gPG GdKHJ GdeHGQc CeI GdNGdb GHfI cGJHg CMeO Hf OGhO Hf SdjeGf GdHjLhQi GdTGaYi ai GdTgQ GdKGfi ef YeQgG s
(3BNQgG (B:s
(3BNQ GdehLhO efg (B: (3jfJgi GdehLhO efg HPcQ SeGY Ydi GdTjN eXaQ GdOjf eMehO Hf GdTjN TgGH GdOjf CMeO GdYfJGHi GdCeTGWi GdMfai JGQjNg SGHY YTQ QeVGf SfI EMOi hJSYjf hKeGfeGjI s
(3Hbde hGdO UGMHI GdKHJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs